HIV and Non‐HIV Patients Have Similar Rates of Neoplastic Findings on Screening Colonoscopy Within a Predominantly African American Cohort - Pooja Mude; Alexandra E. Thomson; Lavannya Atri; Samantha Newman; Carlos Palacio; John Erikson L. Yap; Christian S. Jackson; Kenneth J. Vega (Cancer Medicine)
ABSTRACT Introduction With the reduction in human immunodeficiency virus (HIV)–related mortality secondary to antiretroviral therapy, chronic medical conditions and age‐related cancers account for a larger proportion of mortality among those with HIV. Cancer risk overall remains elevated in HIV patients, and cancer screening data in this population is limited. The primary study aim was to determine whether screening colonoscopy findings differed between HIV and non‐HIV patients. Methods A retrospective review of adults with/without HIV undergoing screening colonoscopy between February 2015 and September 2022 was performed. HIV patients were matched with non‐HIV patients by sex, race, and age, undergoing screening colonoscopy within six business days of their matched patients. Demographic data included age, race, sex, family history of colorectal cancer (CRC), smoking status, alcohol use, along with endoscopic and histologic findings that were compared between the matched pairs. Results Ninety matched pairs of HIV and non‐HIV patients undergoing screening colonoscopy comprised the study population. The study group was 78.9% African American, 55.6% male, with a mean age of 59.0 years in HIV patients and 54.9 years in non‐HIV patients. Procedure indication was average risk screening in 91.1% of patients. No statistically significant differences in screening colonoscopy findings or polyp histology were observed between HIV and non‐HIV patients. Discussion Similar rates of polyps were found at screening colonoscopy regardless of HIV status. CRC screening recommendations are appropriate for the HIV patient population without limitation.